The Effect of Leverage, Liquidity, and Accounting Conservatism on Profit Quality Moderated by Company Size (Empirical Study on Financial Sector Companies in the Sub-Sector of Banks Listed on the Indonesia Stock Exchange for the 2022-2023 Period) - Engel, Atalya Gabriel Sahetapy; Rani, Puspita (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effects of leverage, liquidity, and accounting conservatism on earnings quality with company size as the moderating variable. The study was conducted on financial sector companies with a sub-sector of banks listed on the Indonesian Stock Exchange in 2022-2023. The sample was selected using purposive sampling, and the data that passed the selection process consisted of 42 companies. The results show that leverage and liquidity have no significant effects on earnings quality, while accounting conservatism has an effect on earnings quality. Additionally, company size as the moderating variable can moderate accounting conservatism but not leverage and liquidity in relation to earnings quality.